Maternal lifestyle characteristics and Wilms tumor risk in the offspring: A systematic review and meta-analysis. (August 2020) - Doganis, Dimitrios; Katsimpris, Andreas; Panagopoulou, Paraskevi; Bouka, Panagiota; Bouka, Evdoxia; Moschovi, Maria; Polychronopoulou, Sofia; Papakonstantinou, Evgenia; Tragiannidis, Athanasios; Katzilakis, Nick; Dana, Helen; Antoniadi, Kondilia; et al.
Highlights: There seems to be an inverse association of maternal folate/vitamins supplementation with WT risk. The association of WT with maternal alcohol consumption should be further explored. Modifiable maternal lifestyle factors in the etiology of WT should be further explored. Abstract: Background: Little is known about the etiology of childhood Wilms tumor (WT) and potentially modifiable maternal risk factors, in particular. Methods: Unpublished data derived from the hospital-based, case-control study of the Greek Nationwide Registry for Childhood Hematological Malignancies and Solid Tumors (NARECHEM-ST) were included in an ad hoc conducted systematic literature review and meta-analyses examining the association between modifiable maternal lifestyle risk factors and WT. Eligible data were meta-analysed in separate strands regarding the associations of WT with (a) maternal folic acid and/or vitamins supplementation, (b) alcohol consumption and (c) smoking during pregnancy. The quality of eligible studies was evaluated using the Newcastle-Ottawa Scale. Results: Effect estimates from 72 cases and 72 age- and sex-matched controls contributed by NARECHEM-ST were meta-analysed together with those of another 17, mainly medium size, studies of ecological, case-control and cohort design. Maternal intake of folic acid and/or other vitamins supplements during pregnancy was inversely associated with WT risk (6 studies, OR: 0.78; 95 %CI: 0.69–0.89, I 2 = 5.4 %); of similar size was the association for folic acid intake alone (4 studies, OR: 0.79; 95 %CI: 0.69-0.91, I 2 = 0.0 %), derived mainly from ecological studies. In the Greek study a positive association (OR: 5.31; 95 %CI: 2.00–14.10) was found for mothers who consumed alcohol only before pregnancy vs. never drinkers whereas in the meta-analysis of the four homogeneous studies examining the effect of alcohol consumption during pregnancy the respective overall result showed an OR: 1.60 (4 studies, 95 %CI: 1.28–2.01, I 2 = 0.0 %). Lastly, no association was seen with maternal smoking during pregnancy (14 studies, OR: 0.93; 95 %CI: 0.80–1.09, I 2 = 0.0 %). Conclusions: In the largest to-date meta-analysis, there was an inverse association of maternal folic acid or vitamins supplementation with WT risk in the offspring, derived mainly from ecological studies. The association with maternal alcohol consumption found in our study needs to be further explored whereas no association with maternal smoking was detected. Given the proven benefits for other health conditions, recommendations regarding folic acid supplementation as well as smoking and alcohol cessation should apply. The maternal alcohol consumption associations, however, should be further explored given the inherent limitations in the assessment of exposures of the published studies.